Revitalisasi peran pancasila dalam menangani krisis moralitas generasi muda di era society 5.0 - Tohari, Fachrudin Ad’han (Maliki Interdisciplinary Journal, 2026)
Pancasila has a fundamental role as the moral foundation of the Indonesian nation. Pancasila is a source of relevant ethical values in facing the challenges of the digital era. In the context of very rapid technological development, the young generation must live in a digital environment that is full of opportunities as well as risks, such as the spread of hoaxes, social polarization, and the weakening of digital moral and ethical values. Various studies say that the internalization of Pancasila values in education is still far from optimal, this is due to a learning approach that tends to be normative and less relevant to the digital reality of the younger generation. In fact, the concept of digital citizenship emphasizes the need for a combination of digital literacy competencies and Pancasila moral values as a guideline for behavior in cyberspace. Pancasila with the principles of humanity, social justice, responsibility, and unity is very much in line with the basic values of modern digital ethics such as accountability, constructive freedom, and social responsibility. In the era of Society 5.0, when generation Z, millennials, and Gen Alpha are the largest internet users, the need to integrate the value of Pancasila into digital education practices has become increasingly urgent. Previous studies have highlighted aspects of digital ethics, character education, and digital citizenship separately, but there has been no research that has developed a comprehensive model that combines digital literacy, digital ethics, and the strengthening of national identity based on Pancasila. This research aims to analyze the process of internalizing Pancasila values in digital era education, formulate a Pancasila education model based on digital literacy and ethics, and identify effective pedagogical strategies through PPKn learning. Technology.